Pengaruh Pijat Bayi terhadap Kualitas Tidur Bayi di Wilayah Kerja Puskesmas Sei Langkai Kota Batam - Siti Nurasia; Desi Pramita Sari; Afif D Alba (Jurnal Ventilator, 2024)
The infancy period is a crucial phase for a child's growth and development, where attention to sleep and stimulation is paramount. Sleep disturbances, such as sleeping less than nine hours per night, frequent awakenings, and difficulty returning to sleep, can affect a baby's emotions and development. This study aims to explore the impact of infant massage on the quality of sleep in infants. The method used was a pre-experimental study with a one-group pretest-posttest design, conducted at the Sei Langkai Public Health Center in Batam City from July to August 2023. The sample consisted of 15 infants selected through purposive sampling. The independent variable was infant massage, and the dependent variable was the quality of infant sleep. Data were analyzed using the Shapiro-Wilk normality test and the Wilcoxon test to assess differences before and after the intervention. The results showed a p-value of 0.001, which is less than 0.05, leading to the rejection of the null hypothesis (H0). This indicates that infant massage has a significant effect on the quality of infant sleep. In conclusion, infant massage is effective in improving the quality of infant sleep and can be recommended as an intervention to address sleep disturbances in infants in the Sei Langkai Public Health Center area.